Pelayanan Penumpang Angkutan Udara di Terminal 2 Domestik Bandar Udara Juanda Surabaya - Siti Masrifah (WARTA ARDHIA, 2015)
Indonesia Air Transportation is currently experiencing significant growth in passenger demand. Air transport passenger in 2014 reached 72.6 million people, up 5.6% from the year 2013. Juanda Airport is an airport which is managed by PT. Angkasa Pura I (Persero). Air transport passenger data in Juanda Airport shows the number of passengers in the year 2013 is 1,822,373 passengers and 2014 is 1.740.420 passengers. This research is aimed to determine the service of air passengers in the terminal 2 Juanda Airport in Surabaya. Results shows the index of satisfaction of passenger reached 84%. It this means that the Juanda Airport Management has provide satisfy services to the passengers. Passengers opinion to the airport performance are priorities for improved services is the number and toilet cleanliness, service check-in to departure and amenities, as well as the coolness of the reception area. While expectations are priorities for enhanced passenger services among other things, is the friendly service personnel, vehicle parking, and the number and toilet cleanliness, and service check-in to departure. Keywords: Services, passenger, terminal, domestic, Juanda Airport. Kondisi penerbangan di Indonesia saat ini mengalami pertumbuhan yang signifikan dalam arti peningkatan penumpang angkutan udara di mana tahun 2014 mencapai 72,6 juta orang atau naik 5,6 % dari tahun 2013 sebanyak 68,5 juta orang. Bandara Juanda Surabaya merupakan bandar udara yang dikelola PT. Angkasa Pura I (Persero), menunjukkan data penumpang pada Tahun 2013 sebesar 1.822.373 penumpang dan Tahun 2014 sebesar 1.740.420 penumpang. Maksud pengkajian adalah untuk mengetahui pelayanan penumpang angkutan udara di terminal 2 Bandara Juanda Surabaya. Hasil analisis diperoleh nilai indek kepuasan (satisfaction index) sebesar 84 %, hal ini berarti penyelenggara bandar udara Juanda memberikan pelayanan kepada penumpang sangat memuaskan. Opini penumpang untuk kinerja bandara yang diprioritaskan untuk ditingkatkan layanannya adalah jumlah dan kebersihan toilet, pelayanan check in keberangkatan dan fasilitasnya, serta kesejukan ruang tunggu. Sedangkan harapan penumpang yang diprioritaskan untuk ditingkatkan layanannya diantaranya, adalah pelayanan petugas yang ramah, tempat parkir kendaraan, dan jumlah dan kebersihan toilet, serta pelayanan check in keberangkatan. Kata kunci: pelayanan, penumpang, terminal 2, domestik, bandar udara juanda.